(untitled) (Texas Journal of Philology, Culture and History, 2024)
Babur is one of the great characters of Asiatic history. Boburnoma is a magnificent contribution to the field of literature. ‘Boburnoma’ is exceptional and beautiful. The style of ‘Boburnoma’ is plain, lively and of matter of facts. As a piece of history ‘Boburnoma’ has no equals and as a piece of literature, is has a unique place. This article says us that the ‘Boburnoma’ which stands higher than most of the autobiographies, the world literature has ever producted